2012
DOI: 10.1371/journal.pone.0047530
|View full text |Cite
|
Sign up to set email alerts
|

A Culture-Independent Approach to Unravel Uncultured Bacteria and Functional Genes in a Complex Microbial Community

Abstract: Most microorganisms in nature are uncultured with unknown functionality. Sequence-based metagenomics alone answers ‘who/what are there?’ but not ‘what are they doing and who is doing it and how?’. Function-based metagenomics reveals gene function but is usually limited by the specificity and sensitivity of screening strategies, especially the identification of clones whose functional gene expression has no distinguishable activity or phenotypes. A ‘biosensor-based genetic transducer’ (BGT) technique, which emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…It is increasingly evident that as yet uncultured bacteria can have key roles in the biodegradation and bioremediation of environmental pollutants (Huang et al, 2009;Chen and Murrell, 2010;Wang et al, 2012). In this study, we demonstrated that MMI can be used to recover live cells of key pollutant degraders from a complex microbial community, such as biosludge, and that MRCs can be used for further eco-physiological studies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is increasingly evident that as yet uncultured bacteria can have key roles in the biodegradation and bioremediation of environmental pollutants (Huang et al, 2009;Chen and Murrell, 2010;Wang et al, 2012). In this study, we demonstrated that MMI can be used to recover live cells of key pollutant degraders from a complex microbial community, such as biosludge, and that MRCs can be used for further eco-physiological studies.…”
Section: Discussionmentioning
confidence: 73%
“…Stable isotope probing (SIP) links uncultured microbial cells with the metabolism of specific stable isotope ( 13 C or 15 N)-labelled substrates (Radajewski et al, 2000;Manefield et al, 2002). SIP combined with metagenomics is able to establish a connection between bacterial identity and ecological function (Chen and Murrell, 2010;Wang et al, 2012). SIP requires that stable isotopes such as 13 C and 15 N be incorporated into biomass (DNA, RNA or protein) and therefore has limited success in processes that have no incorporation of stable isotopes into biomass, such as nitrification, denitrification, sulphate reduction, iron reduction, methanogenesis, co-metabolism in consortia or mixed organic carbon anabolism (Bombach et al, 2010;Nelson and Carlson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problem associated with the low recovery of labeled DNA inherent to SIP, amplification methods such as multiple displacement amplification may be used. Employing this method, Wang et al were able to assemble a nag gene cluster responsible for the conversion of naphthalene to salicylate (17). Presumably, this gene cluster was part of the genome of an uncultured Acidovorax sp., which was identified as a prevalent naphthalene degrader in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Although this combination has been rec-ognized as a promising new approach in soil bioremediation studies (16), it has not been frequently implemented thus far (17). In the present study, we investigated the soil bacterial community of a facility collecting the road runoffs of a highway.…”
mentioning
confidence: 99%
“…Biofilm formation offers microbes an entirely different lifestyle weighing against the planktonic state providing protection from external exposures (e.g., antibiotics) for the community [45][46][47][48][49] . Recently, the field of single cell study has developed some breakthroughs allowing characterisation and interrogation of particular microbes at reasonable levels [50][51][52][53][54][55][56][57][58][59][60] . However, these remain insufficient to fulfil the need to study microbial interactions within the microbiome and their surrounding environment.…”
Section: Which Is More Important?mentioning
confidence: 99%